Rapid-onset dystonia-parkinsonism is associated with reduced cerebral blood flow without gray matter changes - Whitlow, Christopher T.; Atcheson, Kyle M.; Snively, Beverly M.; Cook, Jared F.; Kim, Jeongchul; Haq, Ihtsham U.; Sweadner, Kathleen J.; Ozelius, Laurie J.; Brashear, Allison (Frontiers in Neurology, 2023)
Purpose Previous research showed discrete neuropathological changes associated with rapid-onset dystonia-parkinsonism (RDP) in brains from patients with an ATP1A3 variant, specifically in areas that mediate motor function. The purpose of this study was to determine if magnetic resonance imaging methodologies could identify differences between RDP patients and variant-negative controls in areas of the brain that mediate motor function in order to provide biomarkers for future treatment or prevention trials. Methods Magnetic resonance imaging voxel-based morphometry and arterial spin labeling were used to measure gray matter volume and cerebral blood flow, respectively, in cortical motor areas, basal ganglia, thalamus, and cerebellum, in RDP patients with ATP1A3 variants (n = 19; mean age = 37 ± 14 years; 47% female) and variant-negative healthy controls (n = 11; mean age = 34 ± 19 years; 36% female). Results We report age and sex-adjusted between group differences, with decreased cerebral blood flow among patients with ATP1A3 variants compared to variant-negative controls in the thalamus (p = 0.005, Bonferroni alpha level < 0.007 adjusted for regions). There were no statistically significant between-group differences for measures of gray matter volume. Conclusions There is reduced cerebral blood flow within brain regions in patients with ATP1A3 variants within the thalamus. Additionally, the lack of corresponding gray matter volume differences may suggest an underlying functional etiology rather than structural abnormality.